Saúde Mental, Narrativas e Encarceramento: A Alteridade como Condicionante da Pesquisa - Nardi, Henrique Caetano; Guareschi, Neuza Maria de Fátima; Siebra, Adolfo Jesiel; Montenegro, Francisco Valberdan Pinheiro; Galeano, Giovana Barbieri (Revista Polis e Psique, 2021)
Editorial